The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.5539/ass.v6n4p81
|View full text |Cite
|
Sign up to set email alerts
|

Review of Research on Female Physical and Psychological Aggression

Abstract: Several studies conducted on female aggression (physical and psychological) are the primary concern of the review done in this paper. This article contains three parts -the first part focuses on the findings which show that the rate of aggression for male and female are equal, while the second part focuses on the research that reveal the rate of physical aggression is higher in women than men. The third part concerns on studies which have shown higher level of psychological aggression in women compared to men.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…The result of the present study is very much similar the research findings (UN office on Drugs & crime, 2013, Raymond DiGuiseppe et al 2010) which shows male express more physical aggression than females. The present findings do-not follow other researcher findings (Edalati et al 2010) where it was mentioned that females showed more physical aggression than males. It has also revealed that present finding is not in line with other previous studies (Archer 2000), which implies that there is not specific difference between males and females in terms of physical aggression.…”
Section: Resultscontrasting
confidence: 99%
“…The result of the present study is very much similar the research findings (UN office on Drugs & crime, 2013, Raymond DiGuiseppe et al 2010) which shows male express more physical aggression than females. The present findings do-not follow other researcher findings (Edalati et al 2010) where it was mentioned that females showed more physical aggression than males. It has also revealed that present finding is not in line with other previous studies (Archer 2000), which implies that there is not specific difference between males and females in terms of physical aggression.…”
Section: Resultscontrasting
confidence: 99%
“…There is some evidence that the prevalence of psychological disorders [6,7], and behavioral problems [8] among adolescent girls is high. Aggression among adolescent girls is related to serious consequences [9] in various cultures and countries [10][11][12] and its negative impacts has been reported [11,13]. However, aggressive behavior among women has not received widespread attention or concerns [9].…”
Section: Introductionmentioning
confidence: 99%